The burrow. A provocation for the politician - Alici, Luca (Itinerari, 2024)
Starting from the provocation of the burrow, this paper focuses on the ethical-political scope of three suggestions: mediation (in the time of his fatigue), intimacy (in the time of his extroversion), interest (in the time of his possessive declination). In order to do, it draws on Paul Ricoeur’s reflection on living, it deals two modern age provocations in Hobbes and Rousseau and finally it explains some consequences about politics.